2022
DOI: 10.3389/fonc.2022.905548
|View full text |Cite
|
Sign up to set email alerts
|

Risk of human papillomavirus infection and cervical intraepithelial lesions in Chinese renal transplant recipients

Abstract: ObjectiveWhile human papillomavirus (HPV) infection in women is associated with cervical intraepithelial neoplasia and cervical cancer, HPV testing is not often performed in routine practice for renal transplantation patients. The genotype-specific prevalence of HPV and risk factors for HPV infection are still unclear.MethodsFrom 2010 to 2020, patients receiving renal transplantation surgery (referred to as RTRs), who had been screened for HPV infection one year after transplantation were enrolled. A compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…A 2009 study from the Netherlands reported that renal transplant recipients were at a two-to-six-fold increase of CIN and a three-fold increased risk of cervical carcinoma compared to the immunocompetent population [ 70 ]. These findings were also supported by recent studies conducted in Brazil and China [ 71 , 72 ]. Furthermore, women living with human immunodeficiency virus (HIV) are also thought to be at risk due to the inability to clear the HPV infection effectively [ 73 ].…”
Section: Other Risk Factorssupporting
confidence: 88%
“…A 2009 study from the Netherlands reported that renal transplant recipients were at a two-to-six-fold increase of CIN and a three-fold increased risk of cervical carcinoma compared to the immunocompetent population [ 70 ]. These findings were also supported by recent studies conducted in Brazil and China [ 71 , 72 ]. Furthermore, women living with human immunodeficiency virus (HIV) are also thought to be at risk due to the inability to clear the HPV infection effectively [ 73 ].…”
Section: Other Risk Factorssupporting
confidence: 88%